Peran Mahasiswa Magang Mandiri dalam Mendukung Pelaksanaan Program Bakal Calon Kepala Sekolah (BCKS) di Balai Besar Guru dan Tenaga Kependidikan (BBGTK) Sulawesi Selatan - Nurul Fausia; Nur Adila; Ardiansyah; Dr. Hasan S.Pd.I., M.Pd (Pendidikan Al-Gafari, 2025)
This article describes the experiences of independent internship students majoring in Educational Administration in supporting the implementation of the Prospective Principal Program (BCKS) at the Center for Teachers and Education Personnel (BBGTK) in South Sulawesi. The three-month internship (August–October 2025) provided a platform for students to serve the community in the educational sector through direct involvement in the implementation of teacher and education personnel competency improvement programs. Students were involved in various administrative and managerial activities, from preparing activity rundowns, collecting participant data, archiving documents, to assisting in the preparation of activity financial reports. In addition to BCKS activities, students also participated in the In-Depth Learning (PM) program and the Regional Facilitator Technical Guidance (FASDA) for Guidance and Counseling. Through these activities, students gained valuable experience in coordination, communication, and management of education personnel training. These activities have implications for improving students' professional abilities, strengthening their work ethic, and making a real contribution to the smooth running of the institution's programs.